Analisis Keterkaitan Antara Pola Asuh Orang Tua dengan Motivasi Belajar Siswa Kelas V SDN Pengkok 1 Tahun Ajaran 2016/2017 - Irawati, Intan; , Honest Ummi K, S.S., M. Hum (2017)
This research aims to describe and test the magnitude of the relationship between parenting styles with learning motivation of students. This research included quantitative research. The population in this research was class V SD Negeri 1 Pengkok which is 40 students. The sampling techniques used in this research is sampling of saturated, that is all the population serve as samples. Data collection techniques are questionnaire, interview and documentation. Data analysis technique used is regression analysis. The results of data analysis using regression retrieved values thitung (44,069) > ttabel (2,02269) therefore H0 is rejected or can be assumed there is a link between parenting parents against children's learning motivation. Where in parenting that is given on the students improved 1 it will be followed an increase in student learning motivation of 0.939 where the better parenting the better student learning motivation anyway. Variable parenting styles give relative contribution to learning motivation of 96.307% and the effective contribution of 92.5517%. Keywords: parenting styles, learning motivation